Chitosan derived from crab shell waste: A natural coating against anthracnose disease in Capsicum annuum L. (Chilli) - Hardian Susilo Addy; M Azam Baihaqi (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Chitosan, a polysaccharide derived from crustacean shells, serves as a promising natural coating for horticultural products such as chili (Capsicum annuum L.) to control postharvest diseases like anthracnose, caused by Colletotrichum species. This research aimed to extract chitosan from crab shell waste and evaluate its physicochemical properties and efficacy against anthracnose in chili fruit. Chitosan was produced from crab shell waste through demineralization, deproteinization, and deacetylation. The process yielded 32.29% chitosan. Key characteristics of the extracted chitosan included a violet result in the biuret test (indicating protein presence), partial solubility in acetic acid, 0.02% ash content, a melting point of 193.2 °C, 6.87% moisture content, and a low viscosity of 192.9 centipoise (cP). In vitro assays demonstrated that chitosan at a concentration of 2 mg/mL significantly inhibited the growth of Colletotrichum gloeosporioides. In in vivo trials, pure chitosan (2 mg/mL) and shell-derived chitosan (6 mg/mL) slightly prolonged the disease incubation period to 3.67 days and reduced disease severity by 33.33% compared to the control. However, the chitosan coating did not significantly affect fruit shrinkage. These results suggest that while crab shell-derived chitosan has strong antifungal properties, its formulation may need modification to improve physical barrier properties such as moisture retention.